1984
DOI: 10.1111/j.2164-4918.1984.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Counseling Concerns

Abstract: The problems and concerns of cross-cultural counseling and psychotherapy are evaluated. Specific questions are raised along with suggestions for cross-cultural counseling researchers and practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These issues put many concerns surrounding cross-cultural counseling (e.g., research, cosmology, nosology, and testing; cf. Ahia, 1984) into a context in which they can be better understood. This article will introduce these issues and emphasize their importance in training interculturally skilled counselors.…”
mentioning
confidence: 99%
“…These issues put many concerns surrounding cross-cultural counseling (e.g., research, cosmology, nosology, and testing; cf. Ahia, 1984) into a context in which they can be better understood. This article will introduce these issues and emphasize their importance in training interculturally skilled counselors.…”
mentioning
confidence: 99%
“…The importance of culture upon the counselling relationship is well-documented (Ahia, 1984;Atkinson, Morten & Sue, 1993;Carter, 1992;Lowery, 1983;Saleh, 1989;Sue, 1991;Sue & Zane, 1987;Lappin, 1983). These comprised research on most cultural groups including the Asian (Kim, 1985;Jung, 1984;Shon, 1982), but there is no literature on Micronesian culture and its influence on the therapeutic relationship.…”
Section: Helping the Micronesian Clientmentioning
confidence: 99%
“…These concepts are often intertwined and result in inaccurate or misguided conclusions. Ahia (1984) also observed that many researchers of different cultures are not members of the culture that is under investigation. Researchers are often White and middle class, which may result in data analyses being biased, perhaps unknowingly, toward the Western worldview.…”
Section: Cultural Bias In Counselingmentioning
confidence: 99%
“…Also, it must be noted that cultural bias is inherent in psychological tests and inventories. Ahia (1984) suggested that most tests are not applicable across different cultures. Intelligence tests and psychological inventories are often based on the middle-class White culture and therefore are not particularly relevant to Blacks (Smith, 1977).…”
Section: Cultural Bias In Counselingmentioning
confidence: 99%